A Research on Library Space Layout and Intelligent Optimization Oriented to Readers' Needs. (19th May 2022) - Gu, Binli; Tanoue, Kenichi
Abstract : With the rapid development of the Internet age, all walks of life have been affected to a certain extent. The layout of a traditional library is an extremely important part of the library. A good layout can make full use of the space in the library to maximize the use of space and give readers a better sense of experience. It is better to study or work in the library. At the same time, with the rapid development of the Internet, all walks of life have been affected to a certain extent. For the library, the intelligent library based on GA-RFID technology can improve both the readers and the staff in the library. Reading books can improve the efficiency of study or work. In this article, some comparisons are made between the intelligent library based on GA-RFID technology and various types of libraries, and the technology is compared from many aspects, thus reflecting that this technology is beneficial to readers.